Citraan Metafor pada Puisi Tema Covid-19 Karya Anak Sekolah Dasar - Herwan; Ade Anggraini Kartika Devi (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
In making a poem, elementary school children write metaphors in the scale of their understanding. In other words, the metaphors they wrote were natural, not exaggerated, and not too exaggerated. This study aims to analyze and describe the metaphorical imagery in Covid-19 poetry by elementary school children. The research method used is descriptive qualitative. The data source used was in the form of five poems written by elementary school students in grade 6F which were obtained from the website of the Darussalam Batam Foundation. The results shows that the metaphor widely used in a Covid-19 poetry is anthropomorphic metaphor because children tend to compare things with similarities in their personal experiences.